A common congenital immunodeficiency predisposing to infection and atopy in infancy. Issue 10 (October 1983) - Richardson, V F; Larcher, V F; Price, J F
Abstract : Twenty six infants with a congenital immunodeficiency, characterised by failure of their sera to opsonise heat killed bakers' yeast for phagocytosis by normal polymorphonuclear leucocytes, were studied during infancy to determine the frequency of infection and development of atopy. They were compared with controls, matched prospectively for birth date, sex, parental smoking, and atopy and in whom feeding patterns were similar. In 18 of 26 infants the serum defect persisted at age one year. The incidence of infection and atopy, was appreciably greater in the study group than in controls. The 8 children in whom the defect was transient had a similar incidence of infection but a higher incidence of atopy than controls. Eight of 26 mothers and four of 9 fathers tested also had the serum defect, suggesting a strong genetic component. We support the hypothesis that immunodeficiency predisposes to infection and atopy, and that transient immunodeficiency predisposes to atopy.